Schooling, Violent Conflict, and Gender in Burundi - Van Bavel, Jan; Verwimp, Philip (World Bank, Washington, DC, 2013)
This paper investigates the effect of exposure to violent conflict on human capital accumulation in Burundi. It combines a nationwide household survey with secondary sources on the location and timing of the conflict. Only 20 percent of the birth cohorts studied (1971-1986) completed primary education. Depending on the specification, the probability of completing primary schooling for a boy exposed to violent conflict declines by 7 to 17 percentage points compared to a nonexposed boy, with a decline of 11 percentage points in the preferred specification. In addition, exposure to violent conflict reduces the gender gap in schooling, but only for girls from nonpoor households. Forced displacement is one of the channels through which conflict affects schooling. The results are robust to various specifications and estimation methods.